The effect of group investigation model of learning on improving mathematics learning outcomes - Kuratul Aini; Mahsup Mahsup; Vera Mandailina; Abdillah Abdillah; Putri Ayu Febriani (Universitas Sarjanawiyata Tamansiswa, 2024)
The instructional model is a crucial component in the educational process. This study evaluates the effectiveness of the Group Investigation learning model in enhancing students' mathematics outcomes. A quantitative research method with a One Group Pretest-Posttest design was used, involving 29 eighth-grade students. Data were analyzed using SPSS version 25, revealing a pretest score of 0.010 and a posttest score of 0.063 after implementing the Group Investigation model. The average posttest score was 77.91, indicating a significant impact on learning outcomes. Observations over three sessions showed an increase in student participation from 26.97% with an average score of 2.24 in Session I (categorized as